2019
DOI: 10.3748/wjg.v25.i31.4360
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatocellular carcinoma in patients with portal vein tumor thrombosis: Beyond the known frontiers

Abstract: Hepatocellular carcinoma is one of the most frequent malignant tumors worldwide: Portal vein tumor thrombosis (PVTT) occurs in about 35%-50% of patients and represents a strong negative prognostic factor, due to the increased risk of tumor spread into the bloodstream, leading to a high recurrence risk. For this reason, it is a contraindication to liver transplantation and in several prognostic scores sorafenib represents its standard of care, due to its antiangiogenetic action, although it can grant only a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 183 publications
(166 reference statements)
0
84
1
Order By: Relevance
“…The deficiency of powerful drugs and acquired drug resistance are the main reasons. Sorafenib is the only approved targeted drug for LIHC, and it is commonly reported that the drug resistance would be acquired in the process of therapy[ 31 ]. Although researchers have been trying their best to find underlying the mechanisms, there are much more unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of powerful drugs and acquired drug resistance are the main reasons. Sorafenib is the only approved targeted drug for LIHC, and it is commonly reported that the drug resistance would be acquired in the process of therapy[ 31 ]. Although researchers have been trying their best to find underlying the mechanisms, there are much more unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of treatment strategies according to PVTT is provided in Figure 1 [26,34,35,38,41] . In terms of LDLT, within the scope of the present review, recent studies demonstrated LDLT is a viable option to improve [37] , Japan's PVTT portal vein invasion (VP) classification [34,35] . HAIC: hepatic arterial infusion chemotherapy; IFN-alpha 2b: interferon alfa-2b; LT: liver transplantation; RT: radiation therapy; TACE: transarterial chemoembolization; TARE: transarterial radioembolization; 5-FU: 5-fluorouracil.…”
Section: Vascular Invasionmentioning
confidence: 98%
“…However, two classifications are currently valid to effectively assess prognosis and provide guidance for surgical treatment [34] . The Liver Cancer Study Group of Japan differentiates PVTT in four main categories of portal vein invasion, VP1, VP2, VP3, and VP4 [34][35][36] . In a similar fashion, Cheng et al [34] proposed a four-category classification, with the distinction of a category for microscopic portal vein invasion and the allusion of the extension of PVTT involving the superior mesenteric vein or inferior vena cava [37,38] [ Figure 1].…”
Section: Vascular Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, HCC with portal vein tumor thrombosis (PVTT) is believed to be a negative prognostic factor because it increases the likelihood of tumor cell spread into the bloodstreams, resulting in higher chances of recurrence. 5 Previous studies have stated that HCC patients with portal vein invasion have a median survival period of 2.7-4 months without any treatment. 6,7 However, as per recent studies, depending on the patient's baseline performance status, hepatic function, tumor characteristics, the type of therapy could increase the survival duration from 5 months to 5 years.…”
Section: Introductionmentioning
confidence: 99%